Assessing the Impact of the COVID-19 Pandemic on Student Wellbeing at Universities in the United Kingdom: A Conceptual Analysis - Burns, Danielle; Dagnall, Neil; Holt, Maxine (Frontiers in Education, 2020)
Transitioning into the university environment can be both exciting and stressful. Over recent years, uptake to counselling services within universities in the UK have grown given the concurrent rise in mental health difficulties reported. Mental health support in universities in the UK tend to follow a similar format segregated into three areas under the wider umbrella of Student Services: counselling, wellbeing and disability services. For the purpose of this paper, the concept of student wellbeing, a population-level term concerned with positive emotions rather than diagnosed mental health conditions, will be considered in relation to the COVID-19 outbreak. Sars-Cov-2, otherwise referred to as COVID-19, is a novel coronavirus with the first case of an ‘unknown pneumonia’ reported in Wuhan, China in late December 2019. In the UK, university campuses have closed to both students and non-essential staff in an effort to protect them from contracting the virus. The repercussions of this decision have been monumental on the delivery of teaching, relationships and, importantly, the provision of student services. The transition to online learning and assessment has been undertaken rapidly. Online learning, whilst playing a lesser role prior to the pandemic, now constitutes the entirety of a student’s studies. The implications of this are clear; students no longer physically meet teaching staff for supervision or guidance. Whilst the collective trauma of the pandemic will be felt throughout the Higher Education community beyond the immediacy of the outbreak, collective recovery will also occur through mutual support and the rebuilding of the university community. Although the negative outcomes appear stark, some positivity may manifest itself as a result of the forced changes implemented within the university environment. The current paper will perform a conceptual analysis on student wellbeing in UK universities with a specific lens on the psychosocial impact of the global COVID-19 outbreak. Given the repeated call for clarity within the student wellbeing/mental health domain, unpicking the concept in relation to COVID-19 will enable both academics and practitioners to better implement student wellbeing-related interventions in the future.